2020
DOI: 10.1029/2020gl089415
|View full text |Cite
|
Sign up to set email alerts
|

How Old Are Marshes on the East Coast, USA? Complex Patterns in Wetland Age Within and Among Regions

Abstract: Sea-level dynamics, sediment availability, and marine energy are critical drivers of coastal wetland formation and persistence, but their roles as continental-scale drivers remain unknown. We evaluated the timing and spatial variability of wetland formation from new and existing cores collected along the Atlantic and Gulf coasts of the United States. Most basal peat ages occurred after sea-level rise slowed (after~4,000 years before present), but predominance of sea-level rise studies may skew age estimates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Delgado et al, 2013), we know of no other study that documents the widespread and inadvertent creation of tidal marsh via such human actions. However, there is a growing appreciation for marsh expansion in the Northeast USA following European colonization in the 1600s (Braswell et al, 2020).…”
Section: Conceptual Model Of Marsh Creationmentioning
confidence: 99%
“…Delgado et al, 2013), we know of no other study that documents the widespread and inadvertent creation of tidal marsh via such human actions. However, there is a growing appreciation for marsh expansion in the Northeast USA following European colonization in the 1600s (Braswell et al, 2020).…”
Section: Conceptual Model Of Marsh Creationmentioning
confidence: 99%
“…The few existing studies of sediment sourcing to New England marshes have widely ranging conclusions. Kirwan et al (2011) and Braswell et al (2020) proposed that deforestation by European colonists provided an upland sediment source that drove Northeastern marsh expansion in the eighteenth and nineteenth centuries. At the Webhannet River Estuary in Maine, Ward (2004) also concluded that the uplands were a significant modern-day sediment source based on observations of higher suspended sediment concentrations in the upper estuary channel than in the lower estuary.…”
mentioning
confidence: 99%